Antibacterial and Antibiofilm Activity of the Extract and Fractions of Kelakai (Stenochlaena palustris (Burm.F) Bedd) against Methicillin-resistant Staphylococcus aureus - Joko Priyanto Wibowo; Restu Dara Wewengkang; Medina Nurrahmah; Nurul Fajeriyati; Irfan Zamzani; Afif Pranaya Jati (Borneo Journal of Pharmacy, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major concern in healthcare due to its resistance to antibiotics and ability to form biofilms. This study investigated the antibacterial and antibiofilm activity of the extract and fractions of kelakai (Stenochlaena palustris) leaves against MRSA. Phytochemical screening revealed the presence of alkaloids, flavonoids, steroids, tannins, and triterpenoids in S. palustris leaves. The ethanolic extract of S. palustris leaves exhibited dose-dependent antibacterial activity against MRSA at concentrations up to 500 ppm. Among the fractions, the n-hexane fraction exhibited antibacterial activity at 500 and 1000 ppm, while the methanolic fraction showed inhibition only at 1000 ppm. The ethyl acetate fraction did not show any inhibition. All fractions and extract demonstrated antibiofilm activity, with the n-hexane fraction exhibiting the strongest activity (91.33 ± 1.52%) at 125 ppm. The crude extract of S. palustris leaves showed the weakest antibiofilm activity (32.66 ± 8.14%). These findings suggest that S. palustris leaves contain compounds with antibacterial and antibiofilm properties against MRSA, with the n-hexane fraction being the most promising. Further studies are needed to isolate and characterize the active compounds responsible for these activities.